Aplikasi Persamaan Peng–Robinson Dalam Memperkirakan Korelasi Konstanta Kesetimbangan Sistem Gas Kondensat - Alamta Singarimbun; Amiruddin Takda; Tutuka Ariadji (Indonesian Journal of Physics, 2002)
The pressure of gas condensate reservoir will decrease at the production process. The reduction of pressure under dew point causes gases to condensate into two phase systems i.e. vapor-liquid and its composition. The prediction of phase equilibrium constant of vapor liquid and its compositions is obtained by applying Peng-Robinson equation. Especially for component of hepthane plus (C7+), a new correlation is proposed to determine equilibrium constant gas-liquid and its composition. The data used in this study was field data from several gas wells in Sumatera and Java. The results are an equilibrium constant and a composition as a function of pressure, temperature, specific gravity and molecule weight. The use of a new correlation to other components of gas condensate system (C1–C6 and CO2–N2), gives a good agreement with the standard data in a PVT chart.